Smartphone Addiction and Associated Psychological Factors - Pearson, Claire; Hussain, Zaheer (Addicta: The Turkish Journal on Addictions, 2016)
The use of smartphone technology has increased drastically resulting in a risk of addiction to certain web applications, such as social networking sites (SNS) that are easily accessible via smartphones. A major concern regarding the increased use of SNS sites is the risk of an increase in narcissism amongst users of SNS. The present study examined the relationship between smartphone use, narcissistic tendencies, and personality as predictors of smartphone addiction. A self-selected sample of 256 smartphone users (M = 29.2; SD = 9.49) completed an online survey. The results revealed that 13.3% of the sample was classified as addicted to smartphones. Regression analysis revealed that narcissism, openness, neuroticism, and age were linked to smartphone addiction. Therefore, it is suggested that smartphones encourage narcissism, even in non-narcissistic users. Future research requires more in-depth qualitative data, addiction scale comparisons, and comparison of use with, and without, SNS access. Further, it is advised that prospective buyers of smartphones be pre-warned of the potential addictive properties of new technology. Citation: Pearson, C., & Hussain, Z. (2016). Smartphone addiction and associated psychological factors. Addicta: The Turkish Journal on Addictions, 3, 193‒207. http://dx.doi.org/10.15805/addicta.2016.3.0103
Keywords: Smartphone use; Addiction; Narcissism; Social networking sites; Personality; Narcissistic personality disorder